2015
DOI: 10.22146/ijc.21203
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine-Modified Silica for Adsorption of Gold(III)

Abstract: In this research, L-arginine-modified silica (SiO 2 -Arg) with 3-glycidoxypropyl-trimethoxysilane (GPTMS) as the linking agent has been synthesized through sol gel process for adsorption of Au (III) -Arg material as an effective adsorbent for metal ions particularly gold(III). Keywords: silica; modification; L-arginine; adsorption; gold(III) ABSTRAK Dalam penelitian ini, silika termodifikasi L-arginin (SiO 2 -Arg) dengan 3-glisidoksipropil-trimetoksisilan (GPTMS) sebagai penggandeng telah disintesis melalui … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
0
10
0
3
Order By: Relevance
“…Silika memiliki beberapa sifat unik yang tidak dimiliki oleh senyawa anorganik lainnya seperti, sifat adsorpsi dan pertukaran ion yang baik, kestabilan mekanik dan termal tinggi, mudah dimodifikasi dengan senyawa kimia tertentu untuk meningkatkan kinerjanya (Sriyanti et al, 2005). Silika mampu digunakan sebagai adsorben karena memiliki gugus silanol (Si-OH) dan gugus siloksan (Si-O-Si) serta memiliki pori-pori yang luas dan luas permukaan yang khas (Buhani et al, 2009, Hastuti et al, 2015.…”
Section: Pendahuluanunclassified
“…Silika memiliki beberapa sifat unik yang tidak dimiliki oleh senyawa anorganik lainnya seperti, sifat adsorpsi dan pertukaran ion yang baik, kestabilan mekanik dan termal tinggi, mudah dimodifikasi dengan senyawa kimia tertentu untuk meningkatkan kinerjanya (Sriyanti et al, 2005). Silika mampu digunakan sebagai adsorben karena memiliki gugus silanol (Si-OH) dan gugus siloksan (Si-O-Si) serta memiliki pori-pori yang luas dan luas permukaan yang khas (Buhani et al, 2009, Hastuti et al, 2015.…”
Section: Pendahuluanunclassified
“…Then the magnetite suspension was added with 6 mL sodium silicate solution (1:1) and sonicated for 15 min and followed by mechanical stirring for 30 min. After that, the mixture was added with 1 mL GPTMS and stirred for 30 min, and finally 1 mL of 1 M arginine was added and stirred mechanically for 1 h. The mixture was added with 2 M HCl drop wise up to pH 7 (Adapted from Hastuti et al [20]). The gel formed was aged and kept overnight at a room temperature, washed with distilled water and ethanol 3 times, and dried in an oven at 65°C to constant weight.…”
Section: Instrumentationmentioning
confidence: 99%
“…2d is observed absorption at 3474, 1092, 800, 469 cm (Fig. 2f) shows specific bands of silica at 3402, 1090, 795, and 451 cm -1 , assigned to -OH (Si-OH silanol) groups stretching vibration, asymmetric and symmetric stretching and bending vibration of siloxane Si-O(Si-O-Si), respectively [20,26].…”
Section: Functional Groups Of Fe 3 O 4 /Sio 2 -Gptms-argmentioning
confidence: 99%
“…The amino groups can act as an electron-pair donor to the metal ions. As a result, the amine group is able to adsorb metal ions [10][11][12]. The results showed that the adsorption capacity of Cu(II), Ni(II), Pb(II), Cd(II), and Zn(II) increases with increasing nitrogen atom number in the adsorbent [5].…”
Section: ■ Introductionmentioning
confidence: 99%